1989
DOI: 10.1080/00032718908051358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Alkali-Metal Cations On the Protonation Constants of Myo-Inositol Hexakis(Phosphate)

Abstract: Values for the protonation constants of myo-inositol hexakis (ph0sphate) have been determined at 25°C and 0.1 M ionic strength by potentiometry in media containing two different concentrations of Li+, Na', K + and Cs+ salts.The Alog K,,,, values, which correspond to the differences between the constants obtained with and without alkali-metal cations, are considered as being related to the binding ability of the Iigand towards these cations. 703Copyright 0 1989 hy Marcel Dekker, Inc Downloaded by [McMaster U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Bebot-Brigaud [20] and Sala [21] reported studies at T = 293.15 K, Torres et al [22] at T = 310.15 K, De Carli et al [76] at T = 309.15 K and Costello [18] at 301.15 K. Some authors (Bieth [17,75] and Bebot-Brigaud [20]) used (C 2 H 5 ) 4 NClO 4 as background salt, or (C 3 H 7 ) 4 NBr (Costello [18]). Other values are reported in pure water, as in Barrè [77] and Brigando [19], Hoff-Jorgensen [78], Evans [79], De Stefano et al [23].…”
Section: Literature Comparisonmentioning
confidence: 95%
See 1 more Smart Citation
“…Bebot-Brigaud [20] and Sala [21] reported studies at T = 293.15 K, Torres et al [22] at T = 310.15 K, De Carli et al [76] at T = 309.15 K and Costello [18] at 301.15 K. Some authors (Bieth [17,75] and Bebot-Brigaud [20]) used (C 2 H 5 ) 4 NClO 4 as background salt, or (C 3 H 7 ) 4 NBr (Costello [18]). Other values are reported in pure water, as in Barrè [77] and Brigando [19], Hoff-Jorgensen [78], Evans [79], De Stefano et al [23].…”
Section: Literature Comparisonmentioning
confidence: 95%
“…Some authors reported the protonation constants for all the twelve steps, whereas many others have determined less species, often no more than eight. According to Bieth et al [17,75] the phytate protonated species are formed in a very acidic or very basic pH range, therefore the determination of their stability is often not very accurate, also because of the presence of more than one species at the same pH value.…”
Section: Literature Comparisonmentioning
confidence: 99%
“…Moreover, most of the measurements are performed only in a single ionic medium and at a single ionic strength. Indeed our bibliographical research turned up only two papers reporting data at different ionic strengths (but no explanation of effect on phytate protonation was offered) [17,19], and only in an article by Bieth et al [18] is there any attempt to explain the influence of the nature of the ionic medium (alkaline chlorides) on the acid-base properties of phytate. As these authors write in their paper, "the approach attempted in this work must be considered as qualitative.…”
Section: Comparisons With Literaturementioning
confidence: 99%
“…Despite this, few papers report quantitative data on its acid-base properties and interactions with alkali metal ions [3,13,14,15,16,17,18,19,20,21,22]. In order to obtain information on the speciation of phytate in natural aqueous media, one must study its protonation in different supporting electrolytes at different ionic strengths, and its complexes with the major cationic components of natural fluids, i.e., alkali and alkaline earth cations at different concentrations.…”
Section: Introductionmentioning
confidence: 98%
“…However, relatively few studies have been reported in the literature concerning the acidbase properties of phytate as well as its complexing capacity towards metal ions [10,11,12,13,14,15,16,17,18,19,20]: this type of equilibrium reaction has been mainly investigated by combining potentiometry and spectrophotometry with NMR and/or calorimetric methods.…”
Section: Introductionmentioning
confidence: 99%